PENGARUH QUALITY OF WORK LIFE TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASI, TUROVER INTENTION DAN STRES KERJA: STUDI PADA BMT DI KUDUS - Rokhman, Wahibur (EQUILIBRIUM, 2013)
This study was conducted to investigate the effect of quality of work life on job satisfaction, organiSational commitment, turnover intention and job stress among the employees of Baitul Mal wat Tamwil (BMT) in Kudus Regency, Central Java, Indonesia. The study uses a sample of 150 employees from 13 institutions of BMT. The empirical testing indicates that quality of work life has positive effects on both job satisfaction and organizational commitment; whereas there is no significant evidence of the effect of quality of work life on turnover intention and job stress. Implication, limitation and suggestion for future research are discussed.